Language Choice in Film The Architecture of Love: A Study of Code-Switching and Code-Mixing - Grace Naomi Pane; Marlin Steffi Marpaung (Syntax Literate, 2026)
This study examines language choice in the film The Architecture of Love by analyzing instances of code-switching and code-mixing in the characters’ dialogue. The research aims to identify the structural types of bilingual language use and to explore the communicative functions they serve in character interaction. Employing a qualitative descriptive design with qualitative content analysis, the study analyzes 92 bilingual utterances found in the film. The findings indicate that code-mixing occurs more frequently than code-switching, with insertion emerging as the most dominant type. These bilingual practices are distributed across various interactional contexts, including professional or intellectual discussions, emotional exchanges, informal conversations, and cultural or artistic discourse. Furthermore, code-switching and code-mixing function as strategic linguistic resources that enable characters to negotiate meaning, express interpersonal relationships, and respond to situational demands. Overall, the study demonstrates that language choice in cinematic dialogue reflects interactional context and communicative purposes, highlighting the role of bilingual practices in shaping identity and social relations in film discourse